The current state of CO2 flux chamber studies in the Arctic tundra: a review - Virkkala, Anna-Maria; Virtanen, Tarmo; Lehtonen, Aleksi; Rinne, Janne; Luoto, Miska (Progress in Physical Geography: Earth and Environment)
The Arctic tundra plays an important role in the carbon cycle as it stores 50% of global soil organic carbon reservoirs. The processes (fluxes) regulating these stocks are predicted to change due to direct and indirect effects of climate change. Understanding the current and future carbon balance calls for a summary of the level of knowledge regarding chamber-derived carbon dioxide (CO2) flux studies. Here, we describe progress from recently (2000–2016) published studies of growing-season CO2 flux chamber measurements, namely GPP (gross primary production), ER (ecosystem respiration), and NEE (net ecosystem exchange), in the tundra region. We review the study areas and designs along with the explanatory environmental drivers used. Most of the studies were conducted in Alaska and Fennoscandia, and we stress the need for measuring fluxes in other tundra regions, particularly in more extreme climatic, productivity, and soil conditions. Soil respiration and other greenhouse gas measurements were seldom included in the studies. Although most of the environmental drivers of CO2 fluxes have been relatively well investigated (such as the effect of vegetation type and soil microclimate on fluxes), soil nutrients, other greenhouse gases and disturbance regimes require more research as they might define the future carbon balance. Particular attention should be paid to the effects of shrubification, geomorphology, and other disturbance effects such as fire events, and disease and herbivore outbreaks. An improved conceptual framework and understanding of underlying processes of biosphere–atmosphere CO2 exchange will provide more information on carbon cycling in the tundra. 2017